Axonal Regeneration Induced by Blockade of Glial Inhibitors Coupled with Activation of Intrinsic Neuronal Growth Pathways - Wang, Xingxing (2012)
Several pharmacological approaches to promote neural repair and recovery after CNS injury have been identified. Blockade of either astrocyte-derived chondroitin sulfate proteoglycans (CSPGs) or oligodendrocyte-derived NogoReceptor (NgR1) ligands reduces extrinsic inhibition of axonal growth, though combined blockade of these distinct pathways has not been tested. The intrinsic growth potential of adult mammalian neurons can be promoted by several pathways, including pre-conditioning injury for dorsal root ganglion (DRG) neurons and macrophage activation for retinal ganglion cells (RGCs). Singly, pharmacological interventions have restricted efficacy without foreign cells, mechanical scaffolds or viral gene therapy. Here, we examined combinations of pharmacological approaches and assessed the degree of axonal regeneration. After mouse optic nerve crush injury, NgR1-/- neurons regenerate RGC axons as extensively as do zymosan-injected, macrophage-activated WT mice. Synergistic enhancement of regeneration is achieved by combining these interventions in zymosan-injected NgR1-/- mice. In rats with a spinal dorsal column crush injury, a preconditioning peripheral sciatic nerve axotomy, or NgR1(310)ecto-Fc decoy protein treatment or ChondroitinaseABC (ChABC) treatment independently support similar degrees of regeneration by ascending primary afferent fibers into the vicinity of the injury site. Treatment with two of these three interventions does not significantly enhance the degree of axonal regeneration. In contrast, triple therapy combining NgR1 decoy, ChABC and preconditioning, allows axons to regenerate millimeters past the spinal cord injury site. The benefit of a pre-conditioning injury is most robust, but a peripheral nerve injury coincident with, or 3 days after, spinal cord injury also synergizes with NgR1 decoy and ChABC. Thus, maximal axonal regeneration and neural repair is achieved by combining independently effective pharmacological approaches.